Developing a national database for metastatic colorectal cancer management: perspectives and challenges. Issue 11 (November 2013) - Field, K.; Wong, H.‐L.; Shapiro, J.; Kosmider, S.; Tie, J.; Bae, S.; Yip, D.; McKendrick, J.; Nott, L.; Desai, J.; Harold, M.; Lipton, L.; et al.
Abstract Background The changing treatment landscape for metastatic colorectal cancer creates multiple potential treatment strategies. An Australian‐centric database capturing comprehensive information across a range of treatment locations would create a valuable resource enabling multiple important research questions to be addressed. Aims To establish a collection of a consensus dataset capturing treatment and outcomes at multiple public and private hospitals across Australia. Methods An electronic database was developed by a panel of clinicians, to capture an agreed dataset for patients with newly diagnosed metastatic colorectal cancer. Of particular interest were clinician decision‐making, the impact of comorbidities and the frequency of major adverse events. Results Since July 2009, data collection has been established at six public and eight private hospitals across three Australian states and territories. Successful linkage and analysis, with support from BioGrid Australia, of selected data on the initial 864 patients demonstrates that data can be captured from diverse sites, including public and private practice, that multiple factors impact on treatment delivered and outcomes achieved and that comprehensive data on rare but important adverse events can be captured. As a clinical research tool, the project has been highly successful, generating multiple presentations at national and international conferences related to a diverse range of research questions. Conclusions Multistate, project‐specific data collection involving large numbers of patients is achievable. Providing invaluable insight into the routine clinical management of metastatic colorectal cancer in the era of targeted therapies, this also creates a significant resource for research, including many questions not being addressed by clinical trials.